PENGARUH E-SERVICE QUALITY, E-TRUST TERHADAP E- CUSTOMER LOYALTY PADA PENGGUNA LAYANAN KEUANGAN DIGITAL POSPAY DI PT.POS INDONESIA (PERSERO) KCU MANADO - Irene Tesalonika; Efendy Rasjid (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2023)
The rapid development of the scientific and technological revolution in the era of theindustrial revolution 4.0 & 5.0 is currently having an impact on all fields, one of whichhas an impact on the financial services industry. It makes PT. Pos Indonesia as a publicservice facilitator, transformed by launching the digital financial service